Evaluation of nursing students about the objective structured clinical examination - Jéssica Naiara de Medeiros Araújo; Ana Paula Nunes de Lima Fernandes; Raianny Alves Costa; Marcos Antonio Ferreira Júnior; Diana Paula de Souza Rego Pinto Carvalho; Allyne Fortes Vitor (Universidade Federal de Goias, 2015)
The Objective Structured Clinical Examination (OSCE) is considered a fundamental element to improve teaching and learning. It can be understood as a measurement tool of clinical competencies with adoption of standard procedures. A qualitative study aimed to describe the evaluation of students about the OSCE use as strategy to promote the teaching-learning process in Clinical Nursing. A focus group with 27 students was created for data collection with information extracted from three guiding questions. Data was analyzed using Content Analysis technique. Two categories emerged from the first guiding question: the use of SOP; and learning strategy. Three categories emerged from the second question: main feelings; valid experience; and assessment method. From the third question, two categories were identified: learning from errors; and similarity with practice. The OSCE constitutes an assessment strategy that positively contributed with the teaching-learning process in Clinical Nursing.